Cover Feature: Photocatalytic Reduction of CO2 by Highly Efficient Homogeneous FeII Catalyst based on 2, 6‐Bis(1', 2', 3'‐triazolyl‐methyl)pyridine. Comparison with Analogues. (ChemCatChem 23/2022). Issue 23 (11th November 2022) - Gracia, Lisa‐Lou; Barani, Elham; Braun, Jonas; Carter, Anthony B.; Fuhr, Olaf; Powell, Annie K.; Fink, Karin; Bizzarri, Claudia
Abstract : The Cover Feature shows the photo‐driven conversion of CO2 as a water lily pond, where the central role is given by the new iron catalyst, here represented by the white lily. The red flowers symbolize copper‐based photosensitizers, which receive spotlight radiation. In their Research Article, C. Bizzarri and co‐workers describe that photoinduced electron transfer processes are necessary to reduce the catalyst, which is able to reduce carbon dioxide and protons to carbon monoxide and molecular hydrogen, respectively. The selectivity of the CO2 conversion is up to 70%. The developed systems are fully earth‐abundant and produce CO with a maximum apparent quantum yield of 7%. More information can be found in the Research Article by C. Bizzarri and co‐workers .